13. Threshold-tracking TMS without an MEP. Issue 4 (April 2018) - Howells, James; Trinh, Terry; Burke, David; Kiernan, Matthew C.
Abstract : Introduction: Transcranial magnetic stimulation (TMS) is a useful tool for quantifying cortical hyperexcitability in ALS. Short-interval intracortical inhibition (SICI) measures the suppression of descending corticomotoneuronal volleys by GABA-ergic inhibitory interneurons. Threshold-tracking TMS (tt-TMS) studies were developed to overcome the marked variability of motor evoked potentials (MEPs); tt-TMS "tracks" the stimulus intensity required to just evoke a small target MEP. Despite the success of studies using the tt-TMS technique, fasciculations can complicate recordings. Aims: To explore the feasibility of using an accelerometer for the measurement of resting motor threshold (RMT), short interval intracortical inhibition (SICI) and intracortical facilitation (ICF). Methods: Resting motor threshold (RMT), SICI and intracortical facilitation (ICF) were measured in 6 subjects (3M: 3F) using an accelerometer and compared to results recorded with a MEP. The MEP output was recorded over the thenar eminence and amplified (x1k, 2 Hz to 2 kHz) using a purpose-built amplifier. A natus reusable tremor sensory (6.3 mV/g) was fixed to the distal phalanx of digit 1, and its output was amplified with the same amplifier and settings. For both studies an output of 200  μ V was used as the target output measure. RMT in threshold-tracking studies is the magnetic stimulus intensity required to elicit the target MEP (or acceleration). SICI and ICF are measured using a pair of magnetic stimuli with the first stimulus subthreshold (70% of RMT) and the second stimulus tracking the target response. SICI was measured between 1 and 7 ms and ICF between 10 and 30 ms. Results: A low threshold twitch was easily distinguished using an accelerometer, and was fairly insensitive to the orientation of the accelerometer on the thumb. RMT measured using the accelerometer was 56.5 ± 2.3% and 61.2 ± 2.1% for the MEP, though this was not statistically significant ( p  = 0.14). Similarly, average SICI (1–7 ms) was lower (11.2 ± 5.0%) when recorded using the accelerometer and 16.8 ± 6.1% for the MEP ( p  = 0.20). Average ICF(10–30 ms) recorded using the accelerometer was −2.2 ± 3.1% and for MEP 4.7 ± 1.0 ( p  = 0.02). Conclusion: This pilot study shows that an accelerometer provides an easy to use alternative to MEPs for tt-TMS studies. This may be particularly useful early in MND when fasciculations are common and the diagnostic utility of tt-TMS is most beneficial.